1977
DOI: 10.1007/bf00220173
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration in the central nervous system of a pulmonate mollusc, Melampus

Abstract: The left cerebral ganglion was ablated from 72 anesthetized, adult Melampus bidentatus (Mollusca: Pulmonata). Skin incisions were well healed and normal feeding and locomotion observed four days after surgery. Dissections of animals sacrificed weekly showed that most nerves and connectives regrew within 30 days, attaching to the swollen end of the major labial nerve. The enlarged end of this nerve later developed into a distinctive bud; some of these buds contained cell bodies as soon as 42 days after surgery.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Previous authors have taken this latter view because the tentacle ganglion and the conventional CNS have a common embryological origin in the ectodermal cephalic plate (Samassa, 1894;Hanstrom, 1925;ChQtail, 1963). It has recently been demonstrated that the molluscan cerebral ganglia also share with the tentacle ganglion the capability of regeneration (Price, 1977;Moffett, 1980). The evaluation of functional competence involved a test of odor detection in a procedure demanding olfactory orientation behavior.…”
Section: Discuss I0 Nmentioning
confidence: 99%
“…Previous authors have taken this latter view because the tentacle ganglion and the conventional CNS have a common embryological origin in the ectodermal cephalic plate (Samassa, 1894;Hanstrom, 1925;ChQtail, 1963). It has recently been demonstrated that the molluscan cerebral ganglia also share with the tentacle ganglion the capability of regeneration (Price, 1977;Moffett, 1980). The evaluation of functional competence involved a test of odor detection in a procedure demanding olfactory orientation behavior.…”
Section: Discuss I0 Nmentioning
confidence: 99%
“…The gastropod mollusk Melampus bidentatus can regenerate functional neural connections (Moett 1992) and also is able to replace central neurons (Price 1977;Moett and Austin 1982;Moett and Ridgway 1988).…”
Section: Introductionmentioning
confidence: 99%
“…The injured brain spontaneously regenerates its structure, and its function is restored without any exogenous treatment (Price, 1977;Moffett, 1995;Matsuo and Ito, 2010;Matsuo et al, 2010a). The most prominent example is the tentacle of terrestrial pulmonates (Stylommatophora).…”
Section: Introductionmentioning
confidence: 99%